2018
DOI: 10.1002/dneu.22602
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Intrinsic Regenerative Capacity: The Impact of Microtubule Organization and Axonal Transport

Abstract: In the adult vertebrate central nervous system, axons generally fail to regenerate. In contrast, peripheral nervous system axons are able to form a growth cone and regenerate upon lesion. Among the multiple intrinsic mechanisms leading to the formation of a new growth cone and to successful axon regrowth, cytoskeleton organization and dynamics is central. Here we discuss how multiple pathways that define the regenerative capacity converge into the regulation of the axonal microtubule cytoskeleton and transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…In neurons, the MT network is known to participate in neuronal polarization, axonal transport, axonal growth, and regeneration (Murillo and Mendes Sousa, 2018;Janke and Kneussel, 2010). Accordingly, inhibition of HDAC6 in cortical and dorsal root ganglion neurons enhances tubulin acetylation and promotes axon growth, thereby demonstrating the need for stable MTs within axons for cargo delivery (Rivieccio et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In neurons, the MT network is known to participate in neuronal polarization, axonal transport, axonal growth, and regeneration (Murillo and Mendes Sousa, 2018;Janke and Kneussel, 2010). Accordingly, inhibition of HDAC6 in cortical and dorsal root ganglion neurons enhances tubulin acetylation and promotes axon growth, thereby demonstrating the need for stable MTs within axons for cargo delivery (Rivieccio et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Microtubules stability is a major determinant of axonal growth and neuronal polarization during axon formation (Murillo and Sousa, 2018). A previous study had demonstrated that the administration of fibroblast growth factor 13 (FGF13) maintained microtubule stability, and promoted axon formation and neuronal polarization after spinal cord injury (Li et al, 2018).…”
Section: Introductionsmentioning
confidence: 99%
“…While the relationship between increased microtubule dynamics/ reduced microtubule stability and neurite pruning and degeneration is quite intuitive, more complex changes in stability are associated with axon regeneration. First, there are local microtubule changes at the injury site that are important for setting the stage for regeneration (Blanquie & Bradke, 2018;Murillo & Mendes, 2018). In a fun study on Aplysia axons, severing was shown to cause changes in microtubule polarity just proximal to the injury site.…”
Section: Axon Regeneration and Microtubule Stabilit Ymentioning
confidence: 99%